Setting up improvement projects in small scale primary care practices: feasibility of a model for continuous quality improvement. Issue 1 (1st March 1999) - Geboers, H; van der Horst, M; Mokkink, H; van Montfort, P; van den Bosch, W; van den Hoogen, H; Grol, R
Abstract : OBJECTIVES: To evaluate the feasibility of a model for continuous quality improvement in small scale general practice and the improvement projects that practices ran after the introduction of continuous quality improvement. DESIGN: A descriptive study. SETTING: Twenty general practices in the Netherlands tested the model in an intervention period of 18 months. INTERVENTION: A model for continuous quality improvement adapted for general practice was introduced into the practices using a structured strategy. Practices were supported by trained facilitators. MAIN OUTCOME MEASURES: Acceptance at introduction and continued application of the model; the topics of improvement projects that were set up in the practices; whether the improvement projects had been completed; whether they had met the criteria (the use of the "quality cycle" and the Oxford audit score); and whether the self set objectives had been met. RESULTS: The model was introduced and accepted in all participating practices. Practices started 51 improvement projects. At the end of the study period 33 improvement projects had been completed. Practices chose a wide variety of objectives for these projects; most of them concerned medical or organisational topics. Practices started projects mainly because the topic was felt to be a problem or was causing a bottleneck in the organisation. The quality cycle was used in all projects, but practices did not always collect data and evaluate the outcomes. Fourteen projects could be discerned as "full audit". No differences existed in the quality of improvement projects among the various types of practice or between the topics addressed. At the end of the study period half of the practices continued applying the model. CONCLUSION: This study showed that the model was feasible for small scale general practice. However, application of the model tended to disintegrate after the facilitator had left the practice. Practices succeeded reasonably well in running improvement projects. Introduction of continuous quality improvement should particularly focus on this. It is suggested that intensive support is necessary to implement and maintain continuous quality improvement in small scale practices.